2010
DOI: 10.1007/s11434-010-3737-8
|View full text |Cite
|
Sign up to set email alerts
|

Delamination of lamellar phyllosilicate Magadiite

Abstract: 66-4 FIELD Section Title:Surface Chemistry and Colloids Research Institute of Petroleum Processing, SINOPEC, Beijing, Peop. Rep. China. FIELD URL: written in EnglishIn this paper, a new delaminated mesoporous material was prepd. by swelling the lamellar phyllosilicate Magadiite using cetyltrimethylammonium bromide and tetrapropylammonium hydroxide soln., followed by delamination under the cavitation of ultrasonic treatment. Various characterization tools including XRD, N2 adsorption, NMR, IR, SEM and TEM were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…47 Despite these limitations, the delamination/exfoliation of magadiite has been sufficiently studied for its potential benefits in the preparation of hybrid organic-inorganic nanocomposites 109 and optically transparent monoliths. 110 Moreover, Bi et al have successfully obtained high surface area (microporous/mesoporous) materials [111][112][113] via an intermediate delamination of magadiite induced by an intercalation of cetyltrimethylammonium bromide (CTMABr) and tetrapropylammonium hydroxide (TPAOH), ultrasonication in water, followed by acidification, drying and calcination. Similarly, recent developments have shown that the exfoliation of layered sodium octosilicate can also be performed by intercalation of 1-butyl-3-(3-triethoxysilylpropyl)-4,5-dihydroimidazolium and didecyldimethylammonium ions, followed by an ultrasonication in water 114 and pentane, 115 respectively.…”
Section: Preparation Of Delaminated/exfoliated Layered Silicatesmentioning
confidence: 99%
“…47 Despite these limitations, the delamination/exfoliation of magadiite has been sufficiently studied for its potential benefits in the preparation of hybrid organic-inorganic nanocomposites 109 and optically transparent monoliths. 110 Moreover, Bi et al have successfully obtained high surface area (microporous/mesoporous) materials [111][112][113] via an intermediate delamination of magadiite induced by an intercalation of cetyltrimethylammonium bromide (CTMABr) and tetrapropylammonium hydroxide (TPAOH), ultrasonication in water, followed by acidification, drying and calcination. Similarly, recent developments have shown that the exfoliation of layered sodium octosilicate can also be performed by intercalation of 1-butyl-3-(3-triethoxysilylpropyl)-4,5-dihydroimidazolium and didecyldimethylammonium ions, followed by an ultrasonication in water 114 and pentane, 115 respectively.…”
Section: Preparation Of Delaminated/exfoliated Layered Silicatesmentioning
confidence: 99%